2019
DOI: 10.1111/1346-8138.14918
|View full text |Cite
|
Sign up to set email alerts
|

Potential association between rosacea and cancer: A study in a medical center in southern China

Abstract: Growing evidence suggests that rosacea increases the risk of systemic diseases, but studies of the relationships between rosacea and cancer are rare. Aimed to assess the relationship between rosacea and cancer, a total of 7548 patients with confirmed internal malignancies and 8340 cancer‐free individuals aged 18 years or more were included in this study from November 2015 to October 2017. Clinical characteristics, personal history and laboratory data were recorded when patients were diagnosed with rosacea. Log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
(115 reference statements)
1
10
0
Order By: Relevance
“…Here, we were able to show an association not only to metabolic disease, type 2 diabetes, joint problems and ophthalmologic disease, but were able to identify a strong association of rosacea and malignant melanoma as well. When viewed separately from other demographics, our Asian sub-cohort showed no association of rosacea and malignant melanoma, which is in accordance with previous data from Asian working groups 23,24 .…”
Section: Discussionsupporting
confidence: 92%
“…Here, we were able to show an association not only to metabolic disease, type 2 diabetes, joint problems and ophthalmologic disease, but were able to identify a strong association of rosacea and malignant melanoma as well. When viewed separately from other demographics, our Asian sub-cohort showed no association of rosacea and malignant melanoma, which is in accordance with previous data from Asian working groups 23,24 .…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Long et al. 20 found that rosacea is significantly associated with higher incidence of breast cancer and glioma in chinese populations. Moreover, the incidence of AK and keratinocyte carcinoma in patients with rosacea was also increased.…”
Section: Disscussionmentioning
confidence: 88%
“…systemically examined the association between rosacea and cancer in US women and revealed an increased risk of thyroid cancer and basal cell carcinoma in patients with a history of rosacea. Similarly, Long et al 20 . found that rosacea is significantly associated with higher incidence of breast cancer and glioma in chinese populations.…”
Section: Disscussionmentioning
confidence: 89%
“… 8 , 9 In recent years, increasing evidence has suggested a link between inflammatory skin diseases, such as psoriasis and rosacea, and various cancers, including breast cancer. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%